The Constitutional Tribunal and terrorism – an analysis of selected theses from the sentence TK 44/07 - Szczepański, Przemysław (Acta Universitatis Lodziensis. Folia Iuridica, 2012)
The article discuss the main thesis of justification to Polish Constitiutional Tribunal’s judgment k 44/07. The Tribunal expressed the conviction that the fight against terrorism just as the fight against organized crime, or in regular war does not justify the suspension or withdrawal of basic rights and civil liberties. Tribunal notes that the elimination of Article 122 in Polish Aviation Law does not preclude state authorities to respond to the threat described in the disposal of the contested norm. There are other instruments to act in such a situation: The state institution of higher necessity – in the case where the aircraft are occupied by passengers and crew who are not terrorists. Self-defense – in a situation where the aircraft are limited to bombers. Direct provision authorizing the murder of its own citizens by the state has no place in the Polish legal system.